PENDEKATAN EMPLOYEE RELATIONS OLEH PUBLIC RELATIONS (PR) PT. INDAH KIAT PULP AND PAPER TBK DALAM MENSOSIALISASIKAN PROGRAM GO GREEN PADA INTERNAL PERUSAHAAN - Muhammad Irsyad; Nurjanah " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Go Green and Global Warming are two word expression often heard in the last several years. Global warming is the effect which is caused by the inability of the atmosphere in accomodating various kinds of gases thrown up by the earth. Because of that, a company has a responsibility taking care of environment through socializing plantings or it is wellknown as Go Green. One of the company concerns about the environment is through the activity of Go Green campaign. In doing socialization, PR Indah Kiat Pulp and Paper (IKPP) company tried to approach emplyoyees, particularly those who handled employee problems. By applying this strategy, PR could understand the condition directly from the employees, looking at the problems from different points of view so that socialization could run well. This research aimed to look at employee relation approach used by PR Indah KIat Pulp and Paper company in socializing Go Green program at the internal company.This is a descriptive qualitative research. The object of the research was the strategy of employee relations at IKPP company. The researcher used purposive sampling technique to decide the subjects of the research i.e. all informants that fulfilled the research needs. They consisted of 9 persons with key informant the Chief of Public Relation Division Bureau of IKPP company together with the staffs. The techniques used to collect the data were deep observation, interview and documentation.The result of the research was that the socialisation of Go Green program was the strategy planned to show the company concern about the environment through plantation activities which were environmentally friendly. In doing socialization, PR used employee relation approach by applying employee communications strategy, i.e having good communication and interacting each other with employees, employee attitude surveys which functioned as a control and gave evaluation about employee performance, employee counseling which provided consultation and information services needed by employees, and profit sharing as remuneration on the contribution given by employees toward the company. There were also some constraints in applying those strategies, ie. the dense of employee working hours causing limited appropriate time to socialize Go Green program better.Key Words: Employee Relation Approach, „Go Green‟ Program